Improving graphic design skills for HR Center for Self-Help Agriculture and Rural Training (P4S) "Sungai Permai" Lambung Bukit sub-district, Pauh District, West Sumatra - Syukri, Daimon; Rini, Rini; Makky, Muhammad; Halwa, Haniyatul; Dina, Mivtahul (Andalasian International Journal of Social and Entrepreneurial Development, 2022)
In order to increase the promotion of activities and products resulting from the activities of the Self-Help Agriculture and Rural Training Center (P4S) “Sungai Permai” in the Lambung Bukit sub-district, Pauh District, West Sumatra, graphic design training was conducted for one of the members of the farmer group. The training carried out is an introduction and oreration of Corel Draw. The training was carried out for one month involving students from the Department of Food Technology and Agriculture at Andalas University. This training activity can increase the HR capacity of the "Sungai Permai" (P4S) group, which in the future it is hoped that this group will be more independent in terms of developing business and product promotion designs so that they can develop even better.